Fatores endogenos e exogenos que levaram a imigracao/resistencia de pequenos produtores do Distrito de Itaiacoca - Ponga Grossa, na década de 1970 - Silva, José Aparicio da (2008)
This work discusses the relations field-city analyzing the displacement of small farmers in the District of Itaiacoca for the urban perimeter of the city of Ponta Grossa PR, and seeks to dialogue with the small farmers who resisted in Itaiacoca and with entrepreneurs who invested in the district. This event of migration and / or resistance happened more intensely in the decade of seventy of the last century, and during the following decades some events of social, political and economical consequences started to be seen in the urban areas, bringing changes to the life of the rural migrants in touch with city, and to the life of the peasant that started to work with agricultural modernization and rural pluriactivities. In Ponta Grossa, according to the IBGE data, there was an intensity of migration from rural to urban area which marked, in the end of the century, that the amount of population in the city exceeded the amount of people living in the fields. As a result of this process of rural exodus (Itaiacoca to Ponta Grossa - PR) the occupation of Vila Jardim Paraíso could be seen by people that came from Itaiacoca. This choice of occupation of a territory between the city and the countryside features a typical aspect of rurbanity2. Therefore, this work has the aim to identify the endogenous and exogenous factors to the people of the district of Itaiacoca that implied in their decision to migrate to the urban centre or to stand in the rural areas.